The Political Economy of Education in Central Asia Evidence from the Field - Durrani, Naureen; Thibault, Hélène (The Steppe and Beyond: Studies on Central Asia, 2023)
This open access book is intended as an original contribution to the conversation on the role and challenges of education in Central Asia to promote social cohesion by looking at Kazakhstan, Tajikistan and Uzbekistan. Examining education challenges within the countries' wider historical, social, political, and cultural context, the contributions explore existing discourses concerning national identity, religion, language, gender, inclusion, internationalisation of education, and non-state actors through a Political Economy Analysis (PEA) lens. With the understanding that education is both a powerful mechanism of social reproduction in societies and a driver of social change, the book attempts to promote political economy analysis of education as a helpful analytical tool for educational debates and reform agendas in the region and thus will be a valuable resource for policymakers, practitioners, and scholars in this region and beyond. Naureen Durrani is a Professor in School Education at the Graduate School of Education, Nazarbayev University (NU), where she directs the Central Asian Research Centre for Educational Innovation and Transformation (CARCEIT). Before joining NU, she worked at the Centre for International Education, University of Sussex. Hélène Thibault is Associate Professor of Political Science and International Relations at the School of Sciences and Humanities at Nazarbayev University, Kazakhstan. .